A Unified Synthetic Strategy to the Cryptocarya Family of Natural Products Exploiting Anion Relay Chemistry (ARC) - Melillo, Bruno (2013)
[Image: see text] A unified synthetic strategy to the Cryptocarya family of natural products has been achieved employing four-component fragment unions in a “single flask” exploiting Anion Relay Chemistry (ARC). Functionalization of the ARC adducts permits rapid construction of five polyhydroxylated di- and tetrahydropyrone natural products of the Cryptocarya class (1–5), in a total of 7–9 steps from commercially available materials.